2019
DOI: 10.1111/sed.12578
|View full text |Cite
|
Sign up to set email alerts
|

Digital mapping of coastal boulders – high‐resolution data acquisition to infer past and recent transport dynamics

Abstract: Coastal boulder fields provide clues to long‐term frequency‐magnitude patterns of coastal flooding events and have the potential to play an important role in coastal hazard assessment. Mapping boulders in the field is time and labour‐intensive, and work on intertidal reef platforms, as in the present study, is physically challenging. By addressing coastal scientists who are not specialists in remote sensing, this contribution reports on the possibilities and limitations of digital applications in boulder mappi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 46 publications
0
21
0
Order By: Relevance
“…UAVderived orthophotographs and digital surface models (DSMs) can provide excellent data and information on coastal boulder patterns. Orthophotographs allow for the mapping of a axes and b axes, including their orientation, whereas precise values for c axes and boulder volume can be taken from the DSM [50]. In recent years, after an initial decade when the analyses were mostly dedicated to explaining boulder detachment and transport mechanisms and distinguishing between those of tsunamigenic and those of storm origin, boulder studies are now more oriented towards the To investigate the boulder motions on the Premantura Promontory (as the nearshore bathymetry of the model may not be accurate due to a lack of both resolution and accuracy of the bathymetry data), the wave parameters were extracted using a point off Cape Kamenjak, at a depth of about 29 m (Figure 10) and the wave height at the breaking point was calculated using the Sunamura and Horikawa equation [44].…”
Section: Discussionmentioning
confidence: 99%
“…UAVderived orthophotographs and digital surface models (DSMs) can provide excellent data and information on coastal boulder patterns. Orthophotographs allow for the mapping of a axes and b axes, including their orientation, whereas precise values for c axes and boulder volume can be taken from the DSM [50]. In recent years, after an initial decade when the analyses were mostly dedicated to explaining boulder detachment and transport mechanisms and distinguishing between those of tsunamigenic and those of storm origin, boulder studies are now more oriented towards the To investigate the boulder motions on the Premantura Promontory (as the nearshore bathymetry of the model may not be accurate due to a lack of both resolution and accuracy of the bathymetry data), the wave parameters were extracted using a point off Cape Kamenjak, at a depth of about 29 m (Figure 10) and the wave height at the breaking point was calculated using the Sunamura and Horikawa equation [44].…”
Section: Discussionmentioning
confidence: 99%
“…They have been documented around the Mediterranean [72][73][74][75], as well as in the Atlantic on the Aran Islands, Ireland [70,76], the Shetland and Orkney Islands, Scotland [69], Banneg Island, France [77], and Iceland [78]. CBD are also located in both western and northeast Australia [66,79], Iran [80], Oman [81], the Philippines [67,68,82], the Caribbean [71,[83][84][85][86], South Africa [87], and elsewhere. Until recently, however they received little attention: about 90% of published studies are from the last 18 years [88].…”
Section: Coastal Boulder Depositsmentioning
confidence: 99%
“…Data were collected in 2015 and 2017 using a DJI Phantom 3 (FC300X) drone controlled by DJI Groundstation Pro (Table 1). Phantom drones are relatively inexpensive, costing between $400 and $1500, and have been used for similar SfM studies [57,82,101]. Images were collected at nadir along precisely calibrated flightpaths parallel to the coast (Figure 4), at altitude 90 m in 2015 and 50 m in 2017 (Table 1).…”
Section: Image Acquisitionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, in the same location, Spiske et al (2020) also reinterpreted boulder accumulations as remnants of in situ platform denudation that produces shell hash, coral clasts and boulders. Boesl et al (2020) demonstrated how satellite imagery with a sub-metric resolution contributed to a better analysis of boulder dislocation (transport vectors and distances), even in boulder fields which cover larger areas. Highresolution UAV (unmanned aerial vehicle)-based ortho-photographs and digital surface models provided manifold data and information on coastal boulder patterns and can strongly support time-intensive and labour-intensive field surveys.…”
Section: Recent Developments Discussed In This Issuementioning
confidence: 99%